Distinction of mutagenic carcinogens from a mutagenic noncarcinogen in the big blue transgenic mouse. - Cunningham, M L (1996)
The aromatic amines 2,4-diaminotoluene (2,4-DAT) and 2,6-diaminotoluene (2,6-DAT) are structural isomers that have been extensively studied for their mutagenic and carcinogenic characteristics. Both compounds are rapidly absorbed after oral administration and are equally mutagenic in the Ames test; however, 2,4-DAT is a potent hepatocarcinogen, whereas 2,6-DAT does not produce an increased incidence of tumors in rats or mice at similar doses. The Big Blue transgenic B6C3F1 mouse carries multiple copies of the lacl mutational target gene. Our studies were designed to determine whether the Big Blue system could be used to detect differences in the vivo mutagenic activity between the carcinogen-noncarcinogen pair 2,4-DAT and 2,6-DAT and to determine whether the in vivo mutagenesis assay results correspond to the rodent carcinogen bioassay results. Male B6C3F1 transgenic mice were exposed to 2,4-DAT or 2,6-DAT at 0 or 1,000 ppm in the diet for 30 and 90 days or to dimethylnitrosamine as a positive control. Mutant frequencies were nearly identical for all three groups at 30 days, while at 90 days the mutant frequency for the hepatocarcinogen 2,4-DAT (12.1 +/- 1.4 x 10(-5)) was significantly higher (p < 0.01) as compared to both age-matched (spontaneous) controls (5.7 +/- 2.9 x 10(-5)) and the 2,6-DAT-exposed group (5.7 +/- 2.4 x 10(-5)). Results from this study demonstrate that the Big Blue transgenic mutation assay can distinguish differences in vivo between the mutagenic responses of hepatic carcinogens ad a noncarcinogen; is sensitive to mutagens through subchronic dietary exposure; and yields a differential response depending upon the length of time mice are exposed to a mutagen.